An enhanced reversible patient data hiding algorithm for E-healthcare. (February 2021) - Bhardwaj, Rupali
Abstract: The feasibility of future developments in computing technologies strongly relies on the existence of key technologies and their deployments. One of the areas where they are being deployed is telemedicine, it requires communication of patient report to a specialized doctor in a real time scenario. Therefore, any harm to patient medical data can lead to a faulty diagnosis that can be lethal for the patient. To ensure safe and secure communication in E-healthcare framework, a high capacity reversible data hiding algorithm in the encrypted domain has been proposed in this paper. The proposed algorithm gives a higher embedding rate by embedding n binary bits of patient data in b a s e k numeral framework at every pixel of the cover image without any occurrence of underflow and overflow problem. In addition to electronic patient information (EPI), a fragile watermark has been embedded for observing any tamper to the patient data during transmission phase. The experimental study reveals that for all types of test images, proposed method has an embedding rate nearly twice larger than the compared methods, precisely recover EPI with a PSNR value of ∞ dB between the cover image and reconstructed image successfully. Highlights: Average pixel repetition (APR) method is used for interpolation to avoid underflow and overflow problem during data embedding in scaled-up image. The EPI is embedded in b a s e k numeral framework to improve the embedding capacity. Fragile watermark is used for content authentication at the receiver end.